2008
DOI: 10.1111/j.1601-5223.1992.tb00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trivalent and hexavalent chromium on root growth and cell division of Allium cepa

Abstract: The effects of trivalent and hexavalent chromium on root growth, cell division and chromosome morphology of ANium cepa were studied. The concentrations used of chromium nitrate and potassium dichromate were 2 x lo-', 2 x 2 x loW3, 2 x loW4, 2 x loW5, 2 x 10W6, and 2 x 10W7M. The results showed that both trivalent and hexavalent chromium inhibit root growth and cause mitotic irregularities comprising c-mitosis, anaphase bridges, chromosome stickiness, and chromosome fragmentation and lagging. When compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 20 publications
3
34
0
3
Order By: Relevance
“…Chromium toxicity affects the length of the primary roots and promotes changes in the architecture of the entire root system (Samantaray et al, 1996). The inhibitory effect of Cr on root growth (Barbosa et al, 2007) and its toxic effects on cell division result from the fixation of Cr 3+ by plant tissue and disturbances of the osmotic relations that promote restrictions to Ca 2+ transport through the plasma membrane to the cytoplasm (Liu et al, 1992).…”
Section: Coppermentioning
confidence: 99%
“…Chromium toxicity affects the length of the primary roots and promotes changes in the architecture of the entire root system (Samantaray et al, 1996). The inhibitory effect of Cr on root growth (Barbosa et al, 2007) and its toxic effects on cell division result from the fixation of Cr 3+ by plant tissue and disturbances of the osmotic relations that promote restrictions to Ca 2+ transport through the plasma membrane to the cytoplasm (Liu et al, 1992).…”
Section: Coppermentioning
confidence: 99%
“…The Active Mitotic Indices reflects the frequency of cell division and it is regarded as important parameter while determining the rate of root growth (Liu et al 1992). Genotoxicity of heavy metals is reflected by the gradual decrease in Active Mitotic Indices as concentration of doses increased (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of stickiness has been interpreted to be due to depolymerization of DNA (Abraham and Kashy 1979), DNA condensation (Osterberg et al 1984) or physical adhesion of chromosomal proteins (Patil and Bhat 1992). Liu et al (1992), El-Ghamery et al (2000) and Tipirdamaz et al (2003) reported that stickiness reflects a highly toxic and usually irreversible effect that probably leads to cell death.…”
Section: Cytogenetic Analysismentioning
confidence: 99%